A flexible sensor based on MXene material and a preparation method thereof

CN122920971APending Publication Date: 2026-10-16DATONG CO POLYMER (XIAN) TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611134475.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,纯MXene基柔性传感元件在实际服役过程中,存在一定的应用短板:首先,纯MXene材料自身电热传导性能欠佳,导热通路连续性差、热传导效率低,传感器在长期通电、循环形变工作过程中易产生大量焦耳热并发生局部蓄热现象,无法实现快速均匀散热,持续积热会加速纯MXene片层氧化老化,破坏导电网络完整性,造成传感器电阻漂移、传感精度下降、循环稳定性劣化

Benefits of technology

本发明通过添加碳纳米管、MXene材料为主原料,制备得到MXene复合膜。MXene复合膜中碳纳米管一维管状高导热骨架穿插搭接于MXene二维片层间隙之中,可以有效填充纯MXene片层堆叠形成的大量空隙,构筑出连续贯通的立体导热网络,从而解决纯MXene导热通路断裂、热量散出速率慢的缺陷。传感器受压形变时,MXene与碳纳米管形成的复合导电网络发生片层间距变化,依靠稳定的压阻效应输出精准的压力电信号,形变过程中回路产生的焦耳热能够依托复合导热通道快速向外传导释放,有效避免传感膜内部局部热量囤积现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of MXene material, in particular to a flexible sensor based on MXene material and a preparation method thereof.The present application is prepared by adding carbon nanotubes and MXene material as main raw materials to obtain a MXene composite film; then a polyaniline solution formed by polymerization reaction of aniline as main raw material is sprayed on the surface of the MXene composite film to obtain a MXene sensing film layer. The copper foil tape is arranged as a signal layer and a flexible PET layer from inside to outside on both sides of the MXene sensing film layer to obtain a flexible sensor. The hydrophobic paint is sprayed on the surface of the flexible PET layer of the flexible sensor, and the product is obtained after drying, curing and packaging. The product prepared by the present application has good electrothermal property and hydrophobic barrier property, and therefore has wide application prospect in the technical field of MXene material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of MXene material technology, specifically a flexible sensor based on MXene material and its fabrication method. Background Technology

[0002] Flexible strain sensors based on MXene materials, with their unique two-dimensional layered stacked structure and excellent flexible processing characteristics, have significant application value in fields such as human motion monitoring and flexible electronic skin. However, pure MXene-based flexible sensing elements have certain shortcomings in actual service: First, pure MXene materials themselves have poor electrothermal conductivity, poor continuity of the heat conduction path, and low heat conduction efficiency. During long-term power-on and cyclic deformation operation, the sensor is prone to generating a large amount of Joule heat and local heat accumulation, making it impossible to achieve rapid and uniform heat dissipation. Continuous heat accumulation will accelerate the oxidation and aging of pure MXene sheets, destroy the integrity of the conductive network, and cause sensor resistance drift, decreased sensing accuracy, and deterioration of cyclic stability. Secondly, the surface of traditional MXene sensing materials is rich in hydrophilic polar groups. When combined with the PET layer structure, the sensor as a whole does not have good barrier protection capabilities. In high humidity environments, when soaked in sweat, and under slightly corrosive media conditions, water vapor and corrosive impurities can easily penetrate into the sensor, eroding the sensing film layer and the interlayer bonding interface, causing device performance degradation, signal disorder, or even failure. This makes traditional MXene flexible sensors weak in corrosion resistance and short in service life, making them difficult to adapt to complex and humid real-world application scenarios.

[0003] To overcome the shortcomings of existing technologies, this invention provides a flexible sensor based on MXene material and its fabrication method. Summary of the Invention

[0004] The purpose of this invention is to provide a flexible sensor based on MXene material and its fabrication method, so as to solve the problems raised in the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for fabricating a flexible sensor based on MXene material includes the following steps: Step 1: Using carbon nanotubes and MXene as the main raw materials, the mixture is filtered to form a membrane, resulting in an MXene composite membrane; then, a polyaniline solution generated by polymerization of aniline as the main raw material is sprayed onto the surface of the MXene composite membrane to obtain an MXene sensing membrane layer; then, a signal layer and a flexible PET layer are sequentially set on both sides of the MXene sensing membrane layer from the inside out to obtain a flexible sensor. Step 2: Nano-silica is grafted and modified with hexadecyltrimethoxysilane and methyltrimethoxysilane to obtain hydrophobic modified silica; glass flakes are grafted and modified with KH570 to obtain modified glass flakes. Hydrophobic modified silica, modified glass flakes, and ethyl acetate were mixed and ultrasonically dispersed until uniform. Then, polydimethylsiloxane (PDMS) and a curing agent were added and ultrasonically dispersed until uniform to obtain a hydrophobic coating. The hydrophobic coating was sprayed onto the surface of the flexible PET layer of the flexible sensor, dried, cured, and encapsulated to obtain the finished product.

[0006] More preferably, the signal layer is made of either copper foil tape or polyimide film containing interdigitated electrodes; the content of each component of the hydrophobic coating is as follows (by mass): 0.3-0.4 parts hydrophobic modified silica, 0.20-0.25 parts modified glass flakes, 45-50 parts ethyl acetate, 1.5-2.0 parts polydimethylsiloxane, and 0.15-0.20 parts curing agent.

[0007] The optimized preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 25-35 min, then transfer to deionized water and ultrasonically disperse for 1.0-1.5 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 0-2℃ for 24-28 h, after the reaction is completed, wash the product with water until the pH is 5-6, then remove impurities and centrifuge to obtain MXene colloidal solution; Step S2: Mix the carbon nanotube dispersion and MXene colloidal solution, disperse them evenly by ultrasonication, perform a vacuum filtration to form a film, and then dry them to obtain an MXene composite membrane; Step S3: Mix aniline and sulfuric acid solution, and let stand at -5℃~-3℃ for 50-70 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -5℃~-3℃ for 15-20 h; after the reaction is completed, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane.

[0008] In a more optimized manner, in step S1, the mass fraction of the Triton solution is 0.7-1.0%; the mass-volume ratio of multi-walled carbon nanotubes to the Triton solution is 0.5g:(2-3)mL; the mass fraction of concentrated hydrochloric acid is 36-38%; and the mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid is (4-5)g:3g:40mL:40mL. In step S2, the mass ratio of carbon nanotubes to MXene colloid is 1:(2.0-2.5).

[0009] In a more optimized manner, in step S3, the concentration of the sulfuric acid solution is 5 mol / L; the volume ratio of sulfuric acid solution to aniline is 9.6 mL : (0.4-0.5) mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL : (0.5-0.6) g; and the spraying amount of polyaniline solution is 0.1-0.3 mg / cm³. 2 .

[0010] A more optimized preparation process for hydrophobic modified silica is as follows: nano-silica and anhydrous ethanol are mixed and ultrasonically dispersed for 35-40 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia are added and mixed. The mixture is stirred and reacted for 40-50 min. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain hydrophobic modified silica.

[0011] In a more optimized manner, the mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25g:30mL:(0.65-0.70)g:(0.23-0.25)g:0.95g.

[0012] A more optimized preparation process for modified glass flakes is as follows: glass flakes and a mixed solvent are mixed and ultrasonically dispersed for 50-60 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and the mixed solvent are mixed, the pH of the solution is adjusted to 4.0-4.5, and the reaction is stirred for 2.0-2.5 h; then the dispersion is added, and the reaction is continued at 60-65℃ for 3.5-4.0 h; after the reaction is completed, the modified glass flakes are obtained by centrifugation, washing, and drying.

[0013] In a more optimized manner, the mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of (9-10):1; the mass-volume ratio of glass flakes to mixed solvent is (5.0-5.5) g:100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to mixed solvent is (4-5) mL:100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane is (5.0-5.5) g:(4-5) mL.

[0014] The beneficial effects of this invention are: This invention prepares an MXene composite membrane by adding carbon nanotubes and MXene as the main raw materials. In the MXene composite membrane, a one-dimensional tubular high thermal conductivity framework of carbon nanotubes is interwoven and overlapped within the gaps between the two-dimensional MXene sheets. This effectively fills the numerous voids formed by the stacking of pure MXene sheets, constructing a continuous and interconnected three-dimensional thermally conductive network. This overcomes the shortcomings of pure MXene, such as broken thermal conduction pathways and slow heat dissipation. When the sensor is subjected to pressure deformation, the interlayer spacing of the composite conductive network formed by MXene and carbon nanotubes changes. Relying on a stable piezoresistive effect, it outputs a precise pressure signal. The Joule heat generated in the circuit during deformation can be rapidly conducted outward through the composite thermally conductive channels, effectively avoiding localized heat accumulation inside the sensing membrane.

[0015] Furthermore, a polyaniline solution, generated from the polymerization reaction of aniline as the main raw material, is sprayed onto the surface of the MXene composite membrane to obtain the MXene sensing membrane. This structure can simultaneously optimize the pressure sensing characteristics and overall electrothermal performance of the flexible sensor. In terms of pressure response, conductive polyaniline can establish conductive connection sites between the MXene sheet and carbon nanotubes, improving the overall conductive network structure and enhancing the linearity and detection accuracy of the piezoresistive signal. Regarding electrothermal performance, polyaniline fills the interfacial gaps of the composite membrane, effectively reducing interfacial thermal resistance. Combined with the existing thermally conductive framework, it constructs multidimensional heat transfer channels, uniformly dispersing the Joule heat generated during device operation and eliminating localized hotspot accumulation.

[0016] The invention is characterized by sequentially placing copper foil tape as a signal layer and a flexible PET layer on both sides of the MXene sensing film layer from the inside out, thus obtaining a flexible sensor. A hydrophobic coating is then sprayed onto the surface of the flexible PET layer of the flexible sensor, followed by drying, curing, and encapsulation to obtain the finished product. The copper foil tape signal layer on both sides of the sensing layer possesses excellent thermal and electrical conductivity, enabling efficient acquisition of pressure-sensing electrical signals and lateral conduction of heat diffused from the sensing film. Combined with the regular layered stacking structure of the outer flexible PET substrate, this results in a more balanced stress distribution on the sensing film, further optimizing overall thermal stability.

[0017] Furthermore, this hydrophobic coating uses hydrophobically modified nano-silica and silane-grafted modified glass flakes as composite functional fillers, dispersed in ethyl acetate solvent and then mixed with PDMS matrix and curing agent. The nano-silica, co-grafted with hexadecyltrimethoxysilane and methyltrimethoxysilane, has a surface coated with long-chain alkyl groups, exhibiting excellent hydrophobicity. The glass flakes, after KH570 grafting modification, are arranged in a lamellar, interleaved pattern. By working together with the hydrophobically modified nano-silica to fill the internal pores of the coating, they effectively resist the erosion of corrosive media and extend the penetration path of corrosive media. In summary, the uniform dispersion and curing of these two inorganic fillers in the PDMS coating on the PET surface forms a dense, flexible, integrated protective seal. This seal does not hinder the application requirements of substrate deformation and provides long-term protection against external humid air, human sweat, and trace corrosive substances from penetrating the internal structure of the device. It effectively protects the internal MXene, carbon nanotube composite thermal and electrical conductive network, and polyaniline-modified sensing film layer, preventing signal interference and other malfunctions. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Raw material source: Multi-walled carbon nanotubes with a diameter of 10 nm; nano-silica with a size of 20 nm; glass flakes with a size of 120 mesh; polydimethylsiloxane and curing agent are selected from the Dow Corning SYLGARD 184 system, and are compounded according to the mass ratio of matrix resin to matching curing agent of 10:1; one part by mass is 1 g.

[0020] Example 1: Step 1: Carbon nanotubes and MXene materials are used as the main raw materials. After mixing, they are filtered to form a membrane to obtain an MXene composite membrane. Then, a polyaniline solution generated by polymerization of aniline as the main raw material is sprayed onto the surface of the MXene composite membrane to obtain an MXene sensing membrane layer. Copper foil tape as a signal layer and a flexible PET layer are then set on both sides of the MXene sensing membrane layer from the inside to the outside to obtain a flexible sensor. The preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 35 min, then transfer to deionized water and ultrasonically disperse for 1.5 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 2℃ for 28 h, after the reaction, wash the product with water until pH is 5, then remove impurities and centrifuge to obtain MXene colloidal solution; Triton solution mass fraction 1.0%; mass-volume ratio of multi-walled carbon nanotubes to Triton solution 0.5 g: 2.5 mL; concentrated hydrochloric acid mass fraction 36%; mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid 5 g: 3 g: 40 mL: 40 mL; Step S2: The carbon nanotube dispersion and MXene colloidal solution are mixed, ultrasonically dispersed, and then filtered to form a film. After drying, the MXene composite film is obtained; wherein the mass ratio of carbon nanotubes to MXene colloid is 1:2. Step S3: Mix aniline and sulfuric acid solution, let stand at -3℃ for 70 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -3℃ for 20 h. After the reaction is completed, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane; the concentration of sulfuric acid solution is 5 mol / L; the mixing volume ratio of sulfuric acid solution to aniline is 9.6 mL:0.45 mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL:0.55 g; the spraying amount of polyaniline solution is 0.2 mg / cm³. 2 ; Step 2: Mix 0.3g of hydrophobic modified silica, 0.2g of modified glass flakes, and 45g of ethyl acetate. After ultrasonic dispersion, add 1.5g of polydimethylsiloxane (PDMS) and 0.15g of curing agent. After ultrasonic dispersion, obtain a hydrophobic coating. Spray the hydrophobic coating onto the surface of the flexible PET layer of the flexible sensor. After drying, curing, and encapsulation, obtain the finished product. The preparation process of hydrophobic modified silica is as follows: nano-silica and anhydrous ethanol are mixed and ultrasonically dispersed for 40 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia are added and mixed. The mixture is stirred and reacted for 50 min. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain hydrophobic modified silica. The mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25 g: 30 mL: 0.67 g: 0.24 g: 0.95 g. The preparation process of modified glass flakes is as follows: glass flakes and a mixed solvent are mixed and ultrasonically dispersed for 60 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and the mixed solvent are mixed, the pH of the solution is adjusted to 4.0, and the reaction is stirred for 2.5 h. The dispersion is then added, and the reaction is continued at 65℃ for 4.0 h. After the reaction is completed, the modified glass flakes are obtained by centrifugation, washing, and drying. The mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 10:1. The mass-volume ratio of glass flakes to mixed solvent is 5.3 g: 100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to mixed solvent is 4.5 mL: 100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane is 5.3 g: 4.5 mL.

[0021] Example 2: Step 1: Carbon nanotubes and MXene materials are used as the main raw materials. After mixing, they are filtered to form a membrane to obtain an MXene composite membrane. Then, a polyaniline solution generated by polymerization of aniline as the main raw material is sprayed onto the surface of the MXene composite membrane to obtain an MXene sensing membrane layer. Copper foil tape as a signal layer and a flexible PET layer are then set on both sides of the MXene sensing membrane layer from the inside to the outside to obtain a flexible sensor. The preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 30 min, then transfer to deionized water and ultrasonically disperse for 1.2 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 1℃ for 26 h, after the reaction, wash the product with water until pH is 5, then remove impurities and centrifuge to obtain MXene colloidal solution; Triton solution mass fraction 1.0%; mass-volume ratio of multi-walled carbon nanotubes to Triton solution 0.5 g: 2.5 mL; concentrated hydrochloric acid mass fraction 36%; mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid 5 g: 3 g: 40 mL: 40 mL; Step S2: The carbon nanotube dispersion and MXene colloidal solution are mixed, ultrasonically dispersed, and then filtered to form a film. After drying, the MXene composite film is obtained; wherein the mass ratio of carbon nanotubes to MXene colloid is 1:2. Step S3: Mix aniline and sulfuric acid solution, let stand at -4℃ for 60 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -4℃ for 17 h; after the reaction is complete, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane; the concentration of sulfuric acid solution is 5 mol / L; the mixing volume ratio of sulfuric acid solution to aniline is 9.6 mL:0.45 mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL:0.55 g; the spraying amount of polyaniline solution is 0.2 mg / cm³. 2 ; Step 2: Mix 0.3g of hydrophobic modified silica, 0.2g of modified glass flakes, and 45g of ethyl acetate. After ultrasonic dispersion, add 1.5g of polydimethylsiloxane (PDMS) and 0.15g of curing agent. After ultrasonic dispersion, obtain a hydrophobic coating. Spray the hydrophobic coating onto the surface of the flexible PET layer of the flexible sensor. After drying, curing, and encapsulation, obtain the finished product. The preparation process of hydrophobic modified silica is as follows: nano-silica and anhydrous ethanol are mixed and ultrasonically dispersed for 37 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia are added and mixed. The mixture is stirred and reacted for 45 min. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain hydrophobic modified silica. The mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25 g: 30 mL: 0.67 g: 0.24 g: 0.95 g. The preparation process of modified glass flakes is as follows: glass flakes and a mixed solvent are mixed and ultrasonically dispersed for 55 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and the mixed solvent are mixed, the pH of the solution is adjusted to 4.0, and the reaction is stirred for 2.3 h. The dispersion is then added, and the reaction is continued at 63℃ for 3.7 h. After the reaction is completed, the modified glass flakes are obtained by centrifugation, washing, and drying. The mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 10:1. The mass-volume ratio of glass flakes to mixed solvent is 5.3 g: 100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to mixed solvent is 4.5 mL: 100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane is 5.3 g: 4.5 mL.

[0022] Example 3: Step 1: Carbon nanotubes and MXene materials are used as the main raw materials. After mixing, they are filtered to form a membrane to obtain an MXene composite membrane. Then, a polyaniline solution generated by polymerization reaction of aniline as the main raw material is sprayed on the surface of the MXene composite membrane to obtain an MXene sensing membrane layer. Then, copper foil tape as a signal layer and a flexible PET layer are set on both sides of the MXene sensing membrane layer from the inside to the outside to obtain a flexible sensor. The preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 25 min, then transfer to deionized water and ultrasonically disperse for 1.0 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 0℃ for 24 h, after the reaction, wash the product with water until pH is 5, then remove impurities and centrifuge to obtain MXene colloidal solution; Triton solution mass fraction 1.0%; mass-volume ratio of multi-walled carbon nanotubes to Triton solution 0.5 g: 2.5 mL; concentrated hydrochloric acid mass fraction 36%; mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid 5 g: 3 g: 40 mL: 40 mL; Step S2: The carbon nanotube dispersion and MXene colloidal solution are mixed, ultrasonically dispersed, and then filtered to form a film. After drying, the MXene composite film is obtained; wherein the mass ratio of carbon nanotubes to MXene colloid is 1:2. Step S3: Mix aniline and sulfuric acid solution, let stand at -5℃ for 50 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -5℃ for 15 h; after the reaction is complete, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane; the concentration of sulfuric acid solution is 5 mol / L; the mixing volume ratio of sulfuric acid solution to aniline is 9.6 mL:0.45 mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL:0.55 g; the spraying amount of polyaniline solution is 0.2 mg / cm³. 2 ; Step 2: Mix 0.3g of hydrophobic modified silica, 0.2g of modified glass flakes, and 45g of ethyl acetate. After ultrasonic dispersion, add 1.5g of polydimethylsiloxane (PDMS) and 0.15g of curing agent. After ultrasonic dispersion, obtain a hydrophobic coating. Spray the hydrophobic coating onto the surface of the flexible PET layer of the flexible sensor. After drying, curing, and encapsulation, obtain the finished product. The preparation process of hydrophobic modified silica is as follows: nano-silica and anhydrous ethanol are mixed and ultrasonically dispersed for 35 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia are added and mixed. The mixture is stirred and reacted for 40 min. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain hydrophobic modified silica. The mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25 g: 30 mL: 0.67 g: 0.24 g: 0.95 g. The preparation process of modified glass flakes is as follows: glass flakes and a mixed solvent are mixed and ultrasonically dispersed for 50 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and the mixed solvent are mixed, the pH of the solution is adjusted to 4.0, and the reaction is stirred for 2.0 h. The dispersion is then added, and the reaction is continued at 60℃ for 3.5 h. After the reaction is completed, the modified glass flakes are obtained by centrifugation, washing, and drying. The mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 10:1. The mass-volume ratio of glass flakes to mixed solvent is 5.3 g: 100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to mixed solvent is 4.5 mL: 100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane is 5.3 g: 4.5 mL.

[0023] Comparative Example 1: Using only MXene material as raw material, an MXene sensing membrane was prepared. The remaining steps and parameters were the same as in Example 1. The specific steps are as follows: Step 1: Using MXene material as the main raw material, the membrane was formed by filtration to obtain an MXene sensing membrane; then, copper foil tape was sequentially set on both sides of the MXene sensing membrane layer from the inside to the outside as a signal layer and a flexible PET layer to obtain a flexible sensor. The preparation process of the MXene sensing membrane is as follows: Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid are mixed and stirred at 2℃ for 28 hours. After the reaction, the product is washed with water until the pH is 5, and then purified and centrifuged to obtain an MXene colloidal solution. The MXene colloidal solution is filtered to form a membrane, and then dried to obtain the MXene sensing membrane. The mass fraction of concentrated hydrochloric acid is 36%. The mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid is 5g:3g:40mL:40mL. Step 2: Mix 0.3g of hydrophobic modified silica, 0.2g of modified glass flakes, and 45g of ethyl acetate. After ultrasonic dispersion, add 1.5g of polydimethylsiloxane (PDMS) and 0.15g of curing agent. After ultrasonic dispersion, obtain a hydrophobic coating. Spray the hydrophobic coating onto the surface of the flexible PET layer of the flexible sensor. After drying, curing, and encapsulation, obtain the finished product. The preparation process of hydrophobic modified silica is as follows: nano-silica and anhydrous ethanol are mixed and ultrasonically dispersed for 40 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia are added and mixed. The mixture is stirred and reacted for 50 min. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain hydrophobic modified silica. The mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25 g: 30 mL: 0.67 g: 0.24 g: 0.95 g. The preparation process of modified glass flakes is as follows: glass flakes and a mixed solvent are mixed and ultrasonically dispersed for 60 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and the mixed solvent are mixed, the pH of the solution is adjusted to 4.0, and the reaction is stirred for 2.5 h. The dispersion is then added, and the reaction is continued at 65℃ for 4.0 h. After the reaction is completed, the modified glass flakes are obtained by centrifugation, washing, and drying. The mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 10:1. The mass-volume ratio of glass flakes to mixed solvent is 5.3 g: 100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to mixed solvent is 4.5 mL: 100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane is 5.3 g: 4.5 mL.

[0024] Comparative Example 2: The preparation method was the same as in Example 1, except that the process of spraying hydrophobic coating was not introduced. The other steps and parameters remained unchanged. The specific operation is as follows: Step 1: Carbon nanotubes and MXene materials were used as the main raw materials. After mixing, the mixture was filtered to form a membrane, which was then used to obtain an MXene composite membrane. Then, a polyaniline solution generated by the polymerization reaction of aniline as the main raw material was sprayed onto the surface of the MXene composite membrane to obtain an MXene sensing membrane layer. Copper foil tape was then set as a signal layer and a flexible PET layer on both sides of the MXene sensing membrane layer from the inside to the outside to obtain a flexible sensor. The flexible sensor was then encapsulated to obtain the finished product. The preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 35 min, then transfer to deionized water and ultrasonically disperse for 1.5 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 2℃ for 28 h, after the reaction, wash the product with water until pH is 5, then remove impurities and centrifuge to obtain MXene colloidal solution; Triton solution mass fraction 1.0%; mass-volume ratio of multi-walled carbon nanotubes to Triton solution 0.5 g: 2.5 mL; concentrated hydrochloric acid mass fraction 36%; mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid 5 g: 3 g: 40 mL: 40 mL; Step S2: The carbon nanotube dispersion and MXene colloidal solution are mixed, ultrasonically dispersed, and then filtered to form a film. After drying, the MXene composite film is obtained; wherein the mass ratio of carbon nanotubes to MXene colloid is 1:2. Step S3: Mix aniline and sulfuric acid solution, let stand at -3℃ for 70 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -3℃ for 20 h. After the reaction is completed, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane; the concentration of sulfuric acid solution is 5 mol / L; the mixing volume ratio of sulfuric acid solution to aniline is 9.6 mL:0.45 mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL:0.55 g; the spraying amount of polyaniline solution is 0.2 mg / cm³. 2 .

[0025] Testing and experimentation: Pressure-electrothermal performance test: The finished product prepared by this invention is used as a sample. The voltage is set to 3V. First, the initial temperature of the sample surface is tested. Then, a glass rod is pressed on the sample surface for 30s. Then, the glass rod is quickly removed and the surface temperature of the sample is tested again. The pressure-electrothermal performance of the flexible sensor sample is characterized by the temperature change data.

[0026] Hydrophobicity Test: A hydrophobic coating was sprayed onto the surface of the flexible PET layer of the flexible sensor, and after drying and curing, a sample was obtained. The surface wettability of the sample was characterized using a contact angle meter, and the test content was the contact angle of the sample surface (using 5 μL of deionized water). Three different locations on the sample surface were selected for testing, and the average value of the test results was taken as the final contact angle measurement value of the sample. The results are shown in the table below:

[0027] Conclusion: In Examples 1-3, with unchanged dosages and only modified reaction parameters, the performance of the samples showed no significant fluctuations. However, in Comparative Example 1, which used only MXene material to prepare the MXene sensing film, the electrothermal performance of the sample decreased compared to Example 1, with the temperature increasing from 24.4℃ to 53.5℃ after pressure application. This indicates that the carbon nanotube and polyaniline composite effectively improves the overall conductive network structure of the sample, enhancing the detection accuracy of the piezoresistive signal; it also effectively reduces interfacial thermal resistance and, in conjunction with the original thermally conductive framework, constructs a multi-dimensional heat transfer channel. Therefore, the electrothermal performance of the MXene sensing film prepared using only MXene material decreased. Comparative Example 2, without the hydrophobic coating process, showed a significant decrease in hydrophobicity compared to Example 1, exhibiting overall hydrophilicity with a contact angle of 78°. This sample lacks good barrier protection capabilities, allowing water vapor and corrosive impurities to easily penetrate and intrude into the sensor, damaging the sample's structure.

[0028] For those skilled in the art, it is obvious that the present invention is not limited to the details disclosed in the exemplary embodiments described above. The present invention can be implemented in other specific ways without departing from its spirit and essential characteristics. Therefore, the foregoing embodiments should be considered exemplary rather than restrictive from any perspective. The scope of protection of the present invention is defined by the appended claims. Therefore, all variations falling within the meaning and scope of the equivalent elements of the claims should be attributed to the scope of the present invention.

Claims

1. A method for fabricating a flexible sensor based on MXene material, characterized in that: Includes the following steps: Step 1: Using carbon nanotubes and MXene as the main raw materials, the mixture is filtered to form a membrane, resulting in an MXene composite membrane; then, a polyaniline solution generated by polymerization of aniline as the main raw material is sprayed onto the surface of the MXene composite membrane to obtain an MXene sensing membrane layer; then, a signal layer and a flexible PET layer are sequentially set on both sides of the MXene sensing membrane layer from the inside out to obtain a flexible sensor. Step 2: Nano-silica is grafted and modified with hexadecyltrimethoxysilane and methyltrimethoxysilane to obtain hydrophobic modified silica; glass flakes are grafted and modified with KH570 to obtain modified glass flakes. Hydrophobic modified silica, modified glass flakes, and ethyl acetate were mixed and ultrasonically dispersed until uniform. Then, polydimethylsiloxane (PDMS) and a curing agent were added and ultrasonically dispersed until uniform to obtain a hydrophobic coating. The hydrophobic coating was sprayed onto the surface of the flexible PET layer of the flexible sensor, dried, cured, and encapsulated to obtain the finished product.

2. The method for fabricating a flexible sensor based on MXene material according to claim 1, characterized in that: The signal layer is made of either copper foil tape or polyimide film containing interdigitated electrodes; the hydrophobic coating has the following components by mass: 0.3-0.4 parts hydrophobic modified silica, 0.20-0.25 parts modified glass flakes, 45-50 parts ethyl acetate, 1.5-2.0 parts polydimethylsiloxane, and 0.15-0.20 parts curing agent.

3. The method for fabricating a flexible sensor based on MXene material according to claim 1, characterized in that: The preparation process of the MXene sensing membrane is as follows: Step S1: Mix multi-walled carbon nanotubes and Triton solution, grind continuously for 25-35 min, then transfer to deionized water and ultrasonically disperse for 1.0-1.5 h to obtain carbon nanotube dispersion; mix Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid, stir and react at 0-2℃ for 24-28 h, after the reaction is completed, wash the product with water until the pH is 5-6, then remove impurities and centrifuge to obtain MXene colloidal solution; Step S2: Mix the carbon nanotube dispersion and MXene colloidal solution, disperse them evenly by ultrasonication, perform a vacuum filtration to form a film, and then dry them to obtain an MXene composite membrane; Step S3: Mix aniline and sulfuric acid solution, and let stand at -5℃~-3℃ for 50-70 min to obtain aniline solution; mix ammonium persulfate and sulfuric acid solution, stir evenly to obtain ammonium persulfate solution; add ammonium persulfate solution to aniline solution, stir evenly, and continue to react at -5℃~-3℃ for 15-20 h; after the reaction is completed, filter and wash with water to obtain polyaniline solution; spray polyaniline solution onto the surface of MXene composite membrane, and dry to obtain MXene sensing membrane.

4. The method for fabricating a flexible sensor based on MXene material according to claim 3, characterized in that: In step S1, the mass fraction of the Triton solution is 0.7-1.0%; the mass-volume ratio of multi-walled carbon nanotubes to Triton solution is 0.5g:(2-3)mL; the mass fraction of concentrated hydrochloric acid is 36-38%; the mass-volume ratio of Ti3AlC2, LiF, deionized water, and concentrated hydrochloric acid is (4-5)g:3g:40mL:40mL; in step S2, the mass ratio of carbon nanotubes to MXene colloid is 1:(2.0-2.5).

5. The method for fabricating a flexible sensor based on MXene material according to claim 3, characterized in that: In step S3, the concentration of the sulfuric acid solution is 5 mol / L; the volume ratio of sulfuric acid solution to aniline is 9.6 mL : (0.4-0.5) mL; the volume-to-mass ratio of sulfuric acid solution to ammonium persulfate is 10 mL : (0.5-0.6) g; and the spraying amount of polyaniline solution is 0.1-0.3 mg / cm³. 2 .

6. The method for fabricating a flexible sensor based on MXene material according to claim 2, characterized in that: The preparation process of hydrophobic modified silica is as follows: nano silica and anhydrous ethanol are mixed and ultrasonically dispersed for 35-40 min. Then, hexadecyltrimethoxysilane, methyltrimethoxysilane and ammonia are added and mixed. The mixture is stirred and reacted for 40-50 min. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain hydrophobic modified silica.

7. The method for fabricating a flexible sensor based on MXene material according to claim 6, characterized in that: The mass fraction of ammonia is 25%, and the mass-volume ratio of nano-silica, anhydrous ethanol, hexadecyltrimethoxysilane, methyltrimethoxysilane, and ammonia is 0.25g:30mL:(0.65-0.70)g:(0.23-0.25)g:0.95g.

8. The method for fabricating a flexible sensor based on MXene material according to claim 2, characterized in that: The preparation process of modified glass flakes is as follows: glass flakes and mixed solvent are mixed and ultrasonically dispersed for 50-60 min to obtain a dispersion; then γ-methacryloxypropyltrimethoxysilane and mixed solvent are mixed, the pH of the solution is adjusted to 4.0-4.5, and the reaction is stirred for 2.0-2.5 h; then the dispersion is added, and the reaction is continued at 60-65℃ for 3.5-4.0 h; after the reaction is completed, the modified glass flakes are obtained by centrifugation, washing and drying.

9. The method for fabricating a flexible sensor based on MXene material according to claim 8, characterized in that: The mixed solvent was obtained by mixing anhydrous ethanol and deionized water in a volume ratio of (9-10):1; the mass-volume ratio of glass flakes to the mixed solvent was (5.0-5.5) g:100 mL; the volume ratio of γ-methacryloxypropyltrimethoxysilane to the mixed solvent was (4-5) mL:100 mL; and the mass-volume ratio of glass flakes to γ-methacryloxypropyltrimethoxysilane was (5.0-5.5) g:(4-5) mL.

10. A flexible sensor based on MXene material, characterized in that, Prepared by the preparation method according to any one of claims 1-9.